Association between coronary artery disease and clinical outcome in cancer patients: A propensity score matching analysis - Zengfa Huang; Tao Li; Shan Zhang; Bei Jiang; Mei Li; Beibei Cao; Hongfeng Zhang; Zhiqiang Zhou; Zheng Huang; Xiang Wang (Heliyon, 2024)
Objective: The aim of this study was to evaluate the prognostic value of coronary artery disease (CAD) detected by coronary computed tomography angiography (CTA) to predict the risk of all-cause mortality in cancer patients in a propensity score matching (PSM) analysis. Methods: A total of 331 patients who previously had cancer and underwent coronary CTA from January 2015 to December 2019 were included. Multivariate Cox proportional hazards regression analysis and propensity-score matching analysis were performed. The primary endpoint was all-cause of mortality. Results: In total, 125 with CAD and 206 with no CAD during a median follow-up of 3.3 years were included in this study. After PSM, age (HR, 1.040; 95%CI, 1.001–1.081; p = 0.014) and CAD (HR, 2.164; 95%CI, 1.057–4.430; p = 0.035) remained significant factors for all-cause mortality. Conclusion: CAD evaluated by coronary CTA was found to be at higher risk for all-cause mortality in cancer patients. Due to the retrospective design and lack of information on some medical history and treatments, especially immune checkpoint inhibitors, a large-scale prospective study is needed to further determine the prognostic value of coronary CTA in cancer patients.